2018
DOI: 10.4491/eer.2018.144
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitative analysis of four isothiazolinones and 3-iodo-2-propynyl butyl carbamate in hygienic consumer products

Abstract: In this study, extraction, clean-up and instrumental analytical conditions were optimized for identifying and quantifying methyl-, chloromethylbenzi-, octyl-isothiazolinone (MIT, CMIT, BIT, OIT) and 3-iodo-2-propynyl butyl carbamate (IPBC), widely used biocidal active ingredients in human hygiene consumer products. Accuracy of the developed ultrasonic assisted extraction method followed by HPLC/MS analysis for four isothiazolinones and IPBC ranged between 60.4% and 113% in various types of consumer product sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
12
0
2
Order By: Relevance
“…The wide variety of cartridge types and solvents makes the SPE procedure suitable for many polar or nonpolar analytes. For the analysis of isothiazolinones, different SPE stationary phases were used [83,[86][87][88][89][90][91].…”
Section: Analysis and Determination Of Isothiazolinone Biocidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The wide variety of cartridge types and solvents makes the SPE procedure suitable for many polar or nonpolar analytes. For the analysis of isothiazolinones, different SPE stationary phases were used [83,[86][87][88][89][90][91].…”
Section: Analysis and Determination Of Isothiazolinone Biocidesmentioning
confidence: 99%
“…Ultrasound is a key technology in achieving the objective of sustainable "green" chemistry and extraction. UAE has been employed for the extraction of isothiazolinones from solid and liquid samples with a high density and viscosity [87,89,90,[94][95][96].…”
Section: Analysis and Determination Of Isothiazolinone Biocidesmentioning
confidence: 99%
See 1 more Smart Citation
“…These plant extracts can be used separately or combined, and sometimes a shampoo can contain extracts of 7 different plants in its composition. To extract MCI and MI from cosmetics and toiletries, different approaches have been employed, including solid-phase extraction [9, 10], matrix solid-phase dispersion [11], or direct dissolving from sample matrix with different solvents [1215]. However, within the limit of our bibliographic research, we did not find any sample preparation process dealing with the matrix of shampoo containing plant extracts.…”
Section: Introductionmentioning
confidence: 96%
“…But current literature study shows that systematic screening of various classes of biocides in textile matrices has not been performed yet. From the available literature, it is revealed that only few studies have been explored on screening methods of banned antimicrobial agents on textile materials [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%